Pemetaan dan Analisis Tren Angka Kecelakaan di Kota Surabaya - Ahmad Riski Maulana; Kuuni Ulfah Naila El Muna; Harry Asjtanto (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Traffic accidents are one of the biggest causes of death in Indonesia. Factors causing traffic accidents are traffic conditions which are the accumulated interactions of various characteristics of drivers, vehicles, road infrastructure and environmental characteristics. Surabaya has become a metropolis city with several rich business diversity in it. In addition, Surabaya has now become the center of business, trade, industry and education in Indonesia. These activities have an impact on increasing the volume of vehicles in the city of Surabaya. The method used in this research is descriptive observational (ecological study). March 2023. BPBD Surabaya City. In 2020 to 2022 the total number of traffic accidents in the city of Surabaya shows an increase. The results of mapping and analysis of secondary data obtained from BPBD Surabaya City show that there are several sub-districts that have a high rate of traffic accidents, namely Wonokromo Sub-district, Gubeng District, Genteng District, Tegalsari District. So that the sub-district requires greater traffic management efforts to overcome and reduce the incidence of traffic accidents. Surabaya is a city with a high enough accident risk. Based on data on the number of incidents and the number of victims in the city of Surabaya from 2020 to 2022, the trend for the number of accidents every year has increased even though the data distribution is not linear due to several factors. Several factors include human factors, vehicle factors, and road factors.